IMPACT OF THE LOAD RATE ON THE ELASTIC PROPERTIES OF BEECH WOOD SAMPLES AT COMPRESSION TEST IN THE LONGITUDINAL AND TANGENTIAL DIRECTION - Radmanović, Kristijan; Roginić, Robert; Šafran, Branimir; Jug, Matija; Sedlar, Tomislav; Ružica Beljo, Lučić (Innovation in Woodworking Industry and Engineering design, 2019)
Knowledge of dynamic elastic properties of wood is an important precondition for rational and effective exploitation of wood raw material. In this paper, the impact of the load rate on the elastic properties of wood at the compression test in the longitudinal and tangential directions is analyzed. Elastic properties which were determined in this research are the modulus of elasticity, stress and strain at the point of proportionality and specific energy and power of elastic deformation. The research was carried out on beech samples that were prepared with smaller dimensions than prescribed in the norm (DIN EN 408) in order to achieve a more accurate determination of the specific energy and power of elastic deformation. The load rate was varied from 2 to 50 mm/min.